PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES PADA MATERI SOFTWARE KELAS VIII SMP NEGERI 6 SAMARINDA - Alexander, Ricky; Rusdiana, Rusdiana; Saputra, Galih Yudha (LPPM Universitas Bina Bangsa, 2025)
The development of learning media plays a very important role in the lecture process. The purpose of this research is to determine the development of learning media based on Google Sites and to assess the feasibility of the learning media that has been created on Software material for Grade VIII at SMP Negeri 6 Samarinda. This type of research uses the ADDIE development model (Analysis, Design, `Development, Implementation, and Evaluation). Data collection techniques involve observation, interviews, and questionnaires. The data analysis techniques used are qualitative descriptive analysis and quantitative analysis. The subjects involved in the research are 1 material expert, 3 media experts, and eighth-grade students at SMP Negeri 6 Samarinda, while the object of the research is the feasibility of developing learning media using Google Sites for Grade VIII at SMP Negeri 6 Samarinda. The results of the research obtained indicate that the developed learning media is